Power of Entrepreneurs [videorecording]. (Japan Japan Institute of Social and Economic Affairs)
Gives a glimpse of the development of Japan"s post war econmy. It discusses the roles of entrepreneurs like Honda and Sony in the industrialization of Japan after the war.
VHS.
Keywords: Honda Corporation; Sony Corporation; Tokyo Telecommunications; Toshiba Corporation; Industrial management -- Japan; Business people -- Japan; Entrepreneurship -- Japan; Japan -- Economic conditions -- 1945-.; Japan -- Economic policy